Complete characterization of attosecond pulses - Kosik, E; Corner, L; Wyatt, A; Cormier, E; Walmsley, I; Dimauro, L (Taylor and Francis Ltd, 2005)
We review the requirements for achieving full phase and amplitude characterization of attosecond X-ray pulses and propose several methods for carrying out such measurements. We show via numerical simulation that these techniques are capable of retrieving full field information of attosecond pulses and compare their performance and ease of implementation.